Atomically dispersed thermal catalyst and laser preparation method and application thereof
The preparation of atomic-scale dispersed heat dissipation catalyst with a unique structure through laser solid-phase synthesis technology solves the problems of complex catalyst preparation and poor stability in the prior art, and achieves efficient CO2 hydrogenation to methanol reaction, and significantly improves the stability of the catalyst.
Patent Information
- Application Number
- CN202411829836.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-12
AI Technical Summary
In the prior art, the preparation steps of a single-atom catalyst are complex and time-consuming, and the stability of the catalyst is poor in high-temperature thermal catalysis, resulting in unstable catalytic performance.
Atomically dispersed thermal catalysts were prepared by laser solid-phase synthesis technology. By treating materials such as cobalt source, indium source and graphene oxide under laser irradiation, a unique "atomically dispersed Pt-In2O3-Co3O4 composite nano-2D graphene limited-domain sea" structure was formed.
The catalyst was achieved with high stability and excellent thermal catalytic performance of CO2 hydrogenation. The CO2 conversion rate reached 30%, the methanol selectivity was >90%, and there was no inactivation in the 400h reaction.
Smart Images

Figure CN119524875A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal catalysis, and in particular relates to an atomic-level dispersed thermal catalyst and a laser preparation method and application thereof. Background Art
[0002] The massive emission of carbon dioxide (CO2) has caused global warming and ocean acidification, which has become a major challenge facing the development of today's society. In the field of heterogeneous catalysis, single-atom catalysts (SACs) have attracted widespread attention due to their highest atomic utilization efficiency, high catalytic activity and selectivity. However, the application of atomically dispersed catalysts in industrial applications is still in its infancy. The reason is that the preparation steps of single atoms are complicated and cumbersome (including chemical synthesis and multiple high-temperature calcinations, up to 600°C to 900°C), the environmental requirements are strict and time-consuming and labor-intensive, so it is extremely challenging to disperse them at the atomic level in a directional and controllable manner on the carrier. Another major reason is the poor stability of the catalyst under the continuous reaction process. Atomic-dispersed metal atoms are easy to move or aggregate on the carrier, especially under reducing gas conditions such as H2 and CO in high-temperature thermal catalysis, the metal active sites are more likely to fail. At present, in the field of thermal catalysis, the long-term stability of catalysts is a common challenge. For example, in the CO2 hydrogenation to methanol industry, copper-zinc-aluminum (Cu-ZnO-Al2O3) catalysts are relatively mature, but the CO2 conversion rate (10%-30%) is low and the methanol selectivity (about 60%-80%) is not high. The biggest problem with the catalyst is its poor stability. During the high-temperature continuous reaction, the generation of H2O covers the active sites of the catalyst, causing the catalyst to sinter and lead to failure.
[0003] In recent years, researchers have developed new material combinations, unique material structures and new preparation methods to prepare thermal catalysts with high CO2 conversion and methanol selectivity. Patent documents such as CN117960169A and CN118649684A disclose coprecipitation and impregnation methods to prepare single-atom nano-island catalysts. The general characteristics of these synthesis methods are complex processes, many synthesis steps, complex processes, long reaction times and specific conditions, and low preparation efficiency. Moreover, single atoms react in a high temperature environment and are easily aggregated and deactivated, resulting in unstable catalytic performance. However, the thermal catalysts prepared by these methods react in a high temperature environment and are easily aggregated and deactivated, resulting in unstable catalytic performance. Therefore, it is urgent to develop a method for preparing single-atom dispersed materials quickly and efficiently, and the prepared catalytic materials can greatly improve the thermal catalytic stability of CO2 hydrogenation. Summary of the invention
[0004] The main purpose of the present invention is to provide an atomic-level dispersed thermal catalyst and a preparation method and application thereof, so as to overcome the deficiencies of the prior art.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: The embodiment of the present invention provides a laser preparation method of an atomically dispersed thermal catalyst, which comprises: Mixing a cobalt source, a first reducing agent, a first solvent, and graphene oxide and heating them for reaction to obtain a first solution; Mixing an indium source, a second reducing agent, a second solvent and the first solution to form a second solution and performing a hydrothermal reaction to obtain a first solid product; And, applying a suspension containing at least the first solid product and a hexahydrate chloroplatinic acid precursor to a substrate surface and subjecting the substrate to laser irradiation treatment to obtain an atomically dispersed thermal catalyst.
[0006] An embodiment of the present invention also provides an atomically dispersed thermal catalyst prepared by the aforementioned laser preparation method, wherein the thermal catalyst includes graphene, a composite nano-oxide and a single atom of Pt; wherein the graphene forms a confined "sea" structure, the composite nano-oxide serves as a local "island" structure, and the Pt is atomically dispersed on the "island" structure.
[0007] The embodiment of the present invention also provides the use of the aforementioned atomically dispersed thermal catalyst in the preparation of methanol by CO2 hydrogenation.
[0008] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adopts laser solid phase synthesis to produce a novel atomically dispersed catalyst with a unique "atomic-dispersed Pt-"In2O3-Co3O4" composite nano-island-two-dimensional graphene confined sea" structure. This special structure realizes the dynamic confinement effect of single atoms during the thermal catalytic process, greatly improving the stability; (2) The thermal catalyst prepared by the present invention has excellent CO2 hydrogenation thermal catalytic performance. The prepared thermal catalyst exhibits excellent performance such as high CO2 conversion rate (30%), high methanol directional selectivity (90%) and ultra-high stability (400h) in the CO2 hydrogenation to methanol reaction; (3) The thermal catalyst prepared by the present invention has broad prospects for industrial application: the laser solid-phase synthesis method is fast and easy to operate in the ambient atmosphere, and has potential versatility and scalability, which can realize the controllable synthesis and large-scale production of SAC, as well as the efficient conversion and utilization of CO2 resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0010] Figure 1 The atomically dispersed Pt-modified nanocomposite "island-sea" synergistic Pt SA SEM electron microscope image of / In2O3-Co3O4 / rGO catalyst; Figure 2 The atomically dispersed Pt-modified nanocomposite "island-sea" synergistic Pt SA TEM electron microscope photo of / In2O3-Co3O4 / rGO catalyst; Figure 3 The Pt single atom modified nanocomposite "island-sea" synergistic Pt prepared in Example 1 of the present invention SAC AC-STEM spherical aberration electron microscope image of / In2O3-Co3O4 / rGO catalyst; Figure 4 The atomically dispersed Pt-modified nanocomposite "island-sea" synergistic Pt SA Wavelet transform (WT) image of X-ray absorption near edge structure (XANES) spectrum of / In2O3-Co3O4 / rGO catalyst; Figure 5 The Pt single atom / atom cluster synergistically modified nanocomposite "island-sea" synergistic Pt prepared in Example 2 of the present invention SA_AC AC-STEM spherical aberration electron microscope image of / In2O3-Co3O4 / rGO catalyst; Figure 6 The Pt single atom-nanoparticle synergistically modified nanocomposite "island-sea" synergistic Pt SA_AC_NC AC-STEM spherical aberration electron microscope image of / In2O3-Co3O4 / rGO catalyst; Figure 7 The Pt single atom / atom cluster modified nanocomposite "island-sea" synergistic Pt prepared in Example 1 of the present invention SA / In2O3-Co3O4 / rGO catalyst in CO2 hydrogenation reaction (pressure = 3.5MPa, temperature = 300°C, gas hourly space velocity GHSV = 24000cm 3 STP , H2 / CO2= 3 / 1) in catalytic activity and stability test diagram. DETAILED DESCRIPTION
[0011] In view of the defects of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. The main purpose is to use laser solid-phase synthesis technology to prepare a nano "island-sea" synergistic thermal catalyst (Pt SA / In2O3-Co3O4 / rGO), used for efficient hydrogenation of carbon dioxide to methanol, with a CO2 conversion rate of 30% and a methanol selectivity of >90%, showing ultra-long stability without deactivation in 400h reaction. The unique advantage of this new "atomic-level dispersion-composite nano-island-two-dimensional confined sea" catalyst is that it can simultaneously achieve multi-level structure construction and single-atom anchoring modification in one step under the multiple effects of photochemistry, thermal reduction and thermal shock generated by laser, and realize efficient CO2 resource conversion and utilization. This method is fast and easy to operate in the ambient atmosphere, and has potential versatility and scalability, which can realize the controllable synthesis and large-scale production of SAC.
[0012] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0013] Specifically, as one aspect of the technical solution of the present invention, a laser preparation method of an atomically dispersed thermal catalyst includes: Mixing a cobalt source, a first reducing agent, a first solvent, and graphene oxide and heating them for reaction to obtain a first solution; Mixing an indium source, a second reducing agent, a second solvent and the first solution to form a second solution and performing a hydrothermal reaction to obtain a first solid product; And, applying a suspension containing at least the first solid product and a hexahydrate chloroplatinic acid precursor to a substrate surface and subjecting the substrate to laser irradiation treatment to obtain an atomically dispersed thermal catalyst.
[0014] In some preferred embodiments, the laser preparation method specifically includes: mixing a cobalt source, graphene oxide and a first solvent, then adding a first reducing agent dilution solution, mixing and stirring the mixture in a water bath for 8 to 15 hours to obtain a first solution.
[0015] Furthermore, the usage ratio of the cobalt source, the first solvent, the graphene oxide and the first reducing agent dilution solution is 0.002~0.005mol:10~35ml:0.02~0.05g:10~30mL.
[0016] Furthermore, the first reducing agent dilution liquid comprises a hydrazine hydrate dilution liquid, and the hydrazine hydrate dilution liquid comprises hydrazine hydrate and water; wherein the volume ratio of the hydrazine hydrate to water is 3~5:5~8.
[0017] Furthermore, the temperature of the water bath is 80-100°C.
[0018] Further, the cobalt source includes any one or more combinations of cobalt nitrate hexahydrate, cobalt chloride hexahydrate, and cobalt sulfate hexahydrate, but is not limited thereto.
[0019] Further, the first solvent includes ethylene glycol, but is not limited thereto.
[0020] In some preferred embodiments, the laser preparation method specifically comprises: Mixing the indium source, the second reducing agent, the second solvent and the first solution and stirring at room temperature for 30 to 60 minutes to form a second solution; And, the second solution is subjected to a hydrothermal reaction at 120-180° C. for 12-20 hours, and then subjected to centrifugation, washing, and drying to obtain a first solid product.
[0021] Furthermore, the usage ratio of the indium source, the second reducing agent, the second solvent and the first solution is 0.005~0.008mol:0.68~0.85g:60~100mL:0.38~0.58g.
[0022] Furthermore, the second solvent includes ethanol and water; wherein the volume ratio of the ethanol to water is 3~5:5~8.
[0023] Further, the indium source includes any one or more combinations of indium nitrate hexahydrate, indium chloride, and indium sulfate, but is not limited thereto.
[0024] Furthermore, the drying process is carried out at a temperature of 50 to 80° C. and for a time of 8 to 18 hours.
[0025] In some preferred embodiments, the laser preparation method specifically comprises: The first solid product and the aqueous solution of chloroplatinic acid hexahydrate precursor are mixed and stirred for 16 to 24 hours to form a suspension, and then the suspension is brushed on the surface of the substrate and dried naturally; wherein the thickness of the suspension brushed is 100 to 200 μm; And, the obtained carbon paper is subjected to laser irradiation treatment, and then washed and dried to obtain an atomically dispersed thermal catalyst; wherein the laser wavelength used in the laser irradiation treatment is 1064nm, the spot diameter is 260~520μm, the repetition frequency is 10-60kHz, the power is 40~100W, and the scanning speed is 1500~3000mm / s.
[0026] Furthermore, the laser irradiation treatment uses an infrared pulse laser.
[0027] Furthermore, the mass volume ratio of the first solid product to the aqueous solution of chloroplatinic acid hexahydrate precursor is 0.30-0.63 g:20-50 mL, and the concentration of the aqueous solution of chloroplatinic acid hexahydrate precursor is 5-25 mmol / L.
[0028] Furthermore, the aqueous solution of chloroplatinic acid hexahydrate precursor is a mixed solution of chloroplatinic acid hexahydrate and water; the concentration of the aqueous solution of chloroplatinic acid hexahydrate precursor is 5-25 mM.
[0029] Furthermore, the drying process is carried out at a temperature of 30-60° C. and for a time of 2-5 hours.
[0030] In some more specific embodiments, the method for preparing the atomically dispersed thermal catalyst comprises: (1) Cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and hydrazine hydrate dilution ( ), ethylene glycol and graphene oxide (GO) are mixed, stirred evenly, and heated to react for a period of time to obtain solution A; (2) Add hydrated indium nitrate (In(NO3)3·6H2O), urea (CH4N2O), anhydrous ethanol and deionized water to solution A and stir evenly to obtain solution B; (3) Solution B is put into the reaction lining of the reactor for hydrothermal reaction, centrifuged, repeatedly washed, filtered, and dried to obtain precipitate C; (4) Powder C is placed in an aqueous solution of chloroplatinic acid hexahydrate precursor and stirred for a period of time. The suspension is brushed onto carbon paper, taken out, and dried naturally. (5) The dried carbon paper was irradiated with laser in air atmosphere, washed with deionized water, and dried to obtain the composite "island" of In2O3-Co3O4 nano-oxide (Pt) dispersed at the atomic level. The thermal catalyst loaded on the graphene "sea" can be written as Pt SA / In2O3-Co3O4 / rGO.
[0031] Preferably, in step (1), the mass of GO in solution A is 0.02-0.05 g, and cobalt nitrate with a molar concentration of 0.002-0.005 mol is added to 10-35 ml of ethylene glycol, and then 10-30 mL of a mixed solution of hydrazine hydrate and deionized water is added, and the volume ratio is 3-5:5-8 (preferably 3:5) for mixed dilution.
[0032] Preferably, the uniformly mixed solution A in step (1) is stirred in a water bath for 8-15 h.
[0033] Preferably, in the solution B in step (2), the mass of A is 0.38-0.58 g, the molar concentration of indium nitrate is 0.005-0.008 mol, and the urea is 0.68-0.85 g, which are mixed with anhydrous ethanol and 60-100 mL of deionized water, and the volume ratio of anhydrous ethanol: deionized water is 3-5:5-8 (preferably 3:5), and stirred at room temperature for 30-60 min to obtain solution B.
[0034] Preferably, in step (3), B is added to the reaction lining of the reactor, reacted at 120-180° C. for 12-20 h, centrifuged, repeatedly washed with deionized water until the pH of the supernatant is neutral, and filtered to obtain the precipitate C.
[0035] Preferably, the drying in step (3) refers to drying in a forced air oven at 50-80° C. for 8-18 h.
[0036] Preferably, in step (4), 20-50 mL of an aqueous solution of chloroplatinic acid hexahydrate precursor is added to 0.30-0.63 g of powder C, with a concentration of 5-25 mM, and the stirring time is 16-24 h.
[0037] Preferably, the suspension in step (4) is brush-coated on a support carbon paper with a thickness of 100-200 μm, taken out, and dried naturally.
[0038] Preferably, the laser used in step (5) has a wavelength of 1064 nm, a repetition rate of 10 kHz, a power of 40-100 W, a spot diameter of 260-520 μm, and a scanning speed of 1500-3000 mm / s.
[0039] Preferably, the drying in step (5) is performed in a forced air oven at 30-60° C. for 2-5 h.
[0040] As a further improvement of the above scheme, during the laser irradiation in step (5), the laser parameters that can be adjusted include: laser wavelength, laser power, laser pulse width, laser spot size, and laser scanning speed.
[0041] Another aspect of an embodiment of the present invention further provides an atomically dispersed thermal catalyst prepared by the aforementioned laser preparation method, wherein the thermal catalyst includes graphene, a composite nano-oxide and Pt single atoms / atomic clusters; wherein the graphene forms a confined "sea" structure, the composite nano-oxide serves as a local "island" structure, and the Pt single atoms / atomic clusters are atomically dispersed on the "island" structure.
[0042] Furthermore, the composite nano-oxide is formed by In2O3 and Co3O4.
[0043] Furthermore, the thermal catalyst has a three-dimensional structure.
[0044] The present invention adopts laser solid phase synthesis to produce a novel atomically dispersed catalyst with a unique structure - "atomic dispersed Pt- In2O3-Co3O4 composite nano-island - two-dimensional graphene confined sea", in which two-dimensional graphene forms a confined structure (sea), the composite nano-oxide is a local "island" structure, and the metal Pt single atom / atom cluster is dispersed on the "island". The formation of the special structure benefits from the multiple effects of photochemistry, thermal reduction and thermal shock generated by the laser, and the multi-level structure construction and single-atom anchoring modification are achieved in one step. In the process of thermal catalysis, the migration of single atoms in this multi-level special structure only occurs on the "nano-island", and not between multiple "nano-islands", so no obvious agglomeration and sintering will occur at high temperature, realizing the dynamic confinement effect of single atoms in the process of thermal catalysis, greatly improving stability.
[0045] The thermal catalyst prepared by the present invention has excellent CO2 hydrogenation thermal catalytic performance: based on the interaction mechanism of laser and material, a composite nano-oxide structure of single atoms and atomic clusters is designed and constructed, and confined on two-dimensional graphene. Through material selection and structural regulation, excellent CO2 hydrogenation to methanol performance is obtained. The metal precursor salt is directionally adsorbed on the carrier by utilizing the different electronegativity of the oxides, and laser precise regulation of the oxygen vacancy active sites is achieved. The prepared thermal catalyst exhibits excellent performance in the CO2 hydrogenation to methanol reaction, such as high CO2 conversion rate (30%), high methanol directional selectivity (90%) and ultra-high stability (400h).
[0046] Another aspect of an embodiment of the present invention further provides the use of the aforementioned atomically dispersed thermal catalyst in the production of methanol by hydrogenation of CO2.
[0047] The present invention provides a method for laser solid phase synthesis of atomically dispersed catalysts, the catalyst having a unique "island-sea" structure, that is, the carbon matrix forms a confined structure (sea), the composite nano-oxide has a local "island" structure, and the metal single atoms / atomic clusters are dispersed on the "islands", this special structure can greatly improve the stability of the thermal catalytic process. The laser solid phase synthesis of single atoms is to anchor metal atoms on the oxygen vacancies of nano-oxides, and only needs to adjust the laser parameters, precursor salt type, and concentration to finally form a catalytic material with this special structure. In the field of thermal catalysis, such as CO2 hydrogenation to methanol, it has great application prospects.
[0048] The present invention realizes the unique "two-dimensional confined substrate sea-nano composite island-single atom / atom cluster" multi-level microstructure construction and controllable modification anchoring of atomic-level dispersed Pt in one step under solid-phase conditions. The abundant oxygen vacancy defects generated by laser action show significant CO2 conversion rate, methanol directional selectivity and excellent long-term stability in CO2 hydrogenation reaction.
[0049] The present invention provides a method for easily regulating the concentration of metal precursors and laser processing parameters, effectively controlling the bonding form of atoms on oxide nanoparticles, from single atoms, atomic clusters to nanoparticles, to maximize the synergistic catalytic effect. It realizes the laser solid-phase controllable synthesis of catalysts of atomic-level dispersion (single atom-atom cluster-nanoparticle) composite "island-sea" system. It breaks through the technical difficulties of difficult environmental control in traditional synthesis processes, poor controllability of single-atom modification, and difficulty in constructing thermally stable multi-level structures.
[0050] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0051] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0052] Example 1 A method for laser solid phase synthesis of single atom-composite "island-sea" thermal catalysts, the specific steps of which are as follows: (1) 0.02 g GO, 0.002 mol cobalt nitrate hexahydrate, 10 mL diluted hydrazine hydrate and 25 mL ethylene glycol solution were mixed, ultrasonically dispersed to form a uniform solution, stirred evenly, heated and stirred for 8 h to obtain solution A; (2) Add 0.38 g of solution A, 0.005 mol In(NO3)3·6H2O indium nitrate, and 0.68 g of urea to 60 mL of a mixed aqueous solution (anhydrous ethanol: deionized water = 30:50 mL), and stir well to obtain solution B; (3) Solution B was added to the reaction lining of the reactor, reacted at 140°C for 15 h, centrifuged, repeatedly washed with deionized water, and filtered to obtain precipitate C; (4) Place 0.30 g of powder C in 20 mL of chloroplatinic acid hexahydrate precursor aqueous solution and stir for 16 h. The concentration is 5 mM. Apply the suspension on carbon paper with a thickness of 100 μm, remove it, and dry it naturally. (5) The dried carbon paper was irradiated with laser at a wavelength of 1064 nm, a spot diameter of 260 μm, a repetition rate of 10 kHz, a power of 40 W, and a scanning speed of 1500 mm / s. The surface was washed with deionized water. After drying, a Pt single atom-modified “island-sea” synergistic catalyst was obtained, which was denoted as Pt SAC / In2O3-Co3O4 / rGO, morphology Figure 1-Figure 3 As shown, the wavelet transform spectrum of X-ray absorption near edge structure (XANES) is shown in Figure 4 shown.
[0053] The Pt single atom-atom cluster-modified nanocomposite "island-sea" synergistic Pt SA / In2O3-Co3O4 / rGO catalyst in CO2 hydrogenation reaction (pressure = 3.5 MPa, temperature = 300 °C, gas hourly space velocity GHSV = 24000 cm 3 STP , H2 / CO2= 3 / 1), catalytic activity and stability test diagram as shown in Figure 7 shown.
[0054] Example 2 A method for laser solid phase synthesis of atomic / atom cluster-composite "island-sea" thermal catalysts, the specific steps of which are as follows: (1) 0.03 g GO, 0.003 mol cobalt nitrate hexahydrate, 15 mL hydrazine hydrate and 30 mL ethylene glycol solution were mixed, ultrasonically dispersed to form a uniform solution, stirred evenly, heated and stirred for 10 h to obtain solution A; (2) Add 0.45 g of solution A, 0.006 mol In(NO3)3·6H2O indium nitrate, and 0.75 g of urea to a mixed aqueous solution (anhydrous ethanol: deionized water = 30:50 mL), and stir evenly to obtain solution B; (3) Solution B was added to the reaction lining of the reactor, reacted at 140°C for 16 h, centrifuged, repeatedly washed with deionized water, and filtered to obtain precipitate C; (4) Place powder C in 30 mL of 10 mM aqueous solution of chloroplatinic acid hexahydrate precursor and stir for 20 h. Apply the suspension on carbon paper with a thickness of 100 μm, remove it, and dry it naturally. (5) The dried carbon paper was irradiated with laser at a wavelength of 1064 nm, a spot diameter of 420 μm, a repetition rate of 10 kHz, a power of 60 W, and a scanning speed of 2000 mm / s. The surface was washed with deionized water. After drying, a Pt single atom / atom cluster-coordinated "atom-nano island-sea" multi-level structure thermal catalyst was obtained. The morphology is as follows: Figure 5 shown.
[0055] Example 3 A method for laser solid phase synthesis of atomic clusters / nanoparticles-composite "island-sea" thermal catalysts, the specific steps of which are as follows: (1) 0.05 g GO, 0.005 mol cobalt nitrate hexahydrate, 20 mL hydrazine hydrate and 35 mL ethylene glycol solution were mixed, ultrasonically dispersed to form a uniform solution, stirred evenly, heated and stirred for 12 h to obtain solution A; (2) Add 0.55 g of solution A, 0.01 mol In(NO3)3·6H2O cobalt nitrate, and 0.85 g of urea to a mixed aqueous solution (anhydrous ethanol: deionized water = 30:50 mL), and stir evenly to obtain solution B; (3) Solution B was added to the reaction lining of the reactor, reacted at 140°C for 18 h, centrifuged, repeatedly washed with deionized water, and filtered to obtain precipitate C; (4) Place powder C in 40 mL of 20 mM aqueous solution of chloroplatinic acid hexahydrate precursor and stir for 30 h. Apply the suspension on carbon paper with a thickness of 100 μm, remove and dry naturally. The dried carbon paper was irradiated with laser at a wavelength of 1064 nm, a spot diameter of 520 μm, a repetition rate of 10 kHz, a power of 100 W, and a scanning speed of 2500 mm / s. The surface was cleaned with deionized water. After drying, a Pt atomic cluster / nanoparticle-coordinated modified "atom-nano island-sea" multi-level structure thermal catalyst was obtained. The morphology is as follows: Figure 6 shown.
[0056] Example 4 A method for laser solid phase synthesis of atomic / atom cluster-composite "island-sea" thermal catalysts, the specific steps of which are as follows: (1) 0.04 g GO, 0.0035 mol cobalt chloride hexahydrate, 20 mL hydrazine hydrate and 30 mL ethylene glycol solution were mixed, ultrasonically dispersed to form a uniform solution, stirred evenly, heated and stirred for 10 h to obtain solution A; (2) Add 0.45 g of solution A, 0.007 mol In(NO3)3·6H2O indium nitrate, and 0.8 g of urea to a mixed aqueous solution (anhydrous ethanol: deionized water = 36:70 mL), and stir evenly to obtain solution B; (3) Solution B was added to the reaction lining of the reactor, reacted at 145°C for 18 h, centrifuged, repeatedly washed with deionized water, and filtered to obtain precipitate C; (4) Place powder C in 35 mL of 12 mM aqueous solution of chloroplatinic acid hexahydrate precursor and stir for 24 h. Apply the suspension on carbon paper with a thickness of 100 μm, remove and dry naturally. (5) The dried carbon paper was irradiated with laser at a wavelength of 1064 nm, a spot diameter of 350 μm, a repetition rate of 35 kHz, a power of 80 W, and a scanning speed of 3000 mm / s. The surface was cleaned with deionized water and dried to obtain a Pt single atom / atom cluster-coordinated "atom-nano island-sea" multi-level structure thermal catalyst.
[0057] Example 5 A method for laser solid phase synthesis of single atom-composite "island-sea" thermal catalysts, the specific steps of which are as follows: (1) 0.02 g GO, 0.002 mol cobalt chloride hexahydrate, 10 mL diluted hydrazine hydrate and 20 mL ethylene glycol solution were mixed, ultrasonically dispersed to form a uniform solution, stirred evenly, heated and stirred for 8 h to obtain solution A; (2) Add 0.38 g of solution A, 0.005 mol of indium chloride, and 0.68 g of urea to 60 mL of a mixed aqueous solution (anhydrous ethanol: deionized water = 30:50 mL), and stir evenly to obtain solution B; (3) Solution B was added to the reaction lining of the reactor, reacted at 140°C for 20 h, centrifuged, repeatedly washed with deionized water, and filtered to obtain precipitate C; (4) Place 0.30 g of powder C in 20 mL of chloroplatinic acid hexahydrate precursor aqueous solution and stir for 16 h. The concentration is 5 mM. Apply the suspension on carbon paper with a thickness of 200 μm, remove it, and dry it naturally. (5) The dried carbon paper was irradiated with laser at a wavelength of 1064 nm, a spot diameter of 300 μm, a repetition rate of 10 kHz, a power of 40 W, and a scanning speed of 1500 mm / s. The surface was cleaned with deionized water and dried to obtain a Pt single atom-modified "atom-nano island-sea" synergistic catalyst.
[0058] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0059] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A laser preparation method for atomically dispersed thermal catalysts, characterized in that: include: Mixing a cobalt source, a first reducing agent, a first solvent, and graphene oxide and heating them for reaction to obtain a first solution; Mixing an indium source, a second reducing agent, a second solvent and the first solution to form a second solution and performing a hydrothermal reaction to obtain a first solid product; And, applying a suspension containing at least the first solid product and a hexahydrate chloroplatinic acid precursor to a substrate surface and subjecting the substrate to laser irradiation treatment to obtain an atomically dispersed thermal catalyst.
2. The laser preparation method according to claim 1, characterized in that: Specifically include: The cobalt source, graphene oxide and the first solvent are mixed, and then the first reducing agent dilution solution is added and mixed, and stirred in a water bath for 8 to 15 hours to obtain a first solution.
3. The laser preparation method according to claim 2, characterized in that: The usage ratio of the cobalt source, the first solvent, the graphene oxide and the first reducing agent dilution is 0.002-0.005 mol: 10-35 ml: 0.02-0.05 g: 10-30 mL; And / or, the first reducing agent dilution liquid comprises a hydrazine hydrate dilution liquid, and the hydrazine hydrate dilution liquid comprises hydrazine hydrate and water; wherein the volume ratio of the hydrazine hydrate to water is 3-5:5-8; And / or, the temperature of the water bath is 80-100°C; And / or, the cobalt source includes any one or more of cobalt nitrate hexahydrate, cobalt chloride hexahydrate, and cobalt sulfate hexahydrate; And / or, the first solvent comprises ethylene glycol.
4. The laser preparation method according to claim 1, characterized in that: Specifically include: Mixing the indium source, the second reducing agent, the second solvent and the first solution and stirring at room temperature for 30 to 60 minutes to form a second solution; And, the second solution is subjected to a hydrothermal reaction at 120-180° C. for 12-20 hours, and then subjected to centrifugation, washing, and drying to obtain a first solid product.
5. The laser preparation method according to claim 4, characterized in that: The dosage ratio of the indium source, the second reducing agent, the second solvent and the first solution is 0.005-0.008 mol: 0.68-0.85 g: 60-100 mL: 0.38-0.58 g; and / or, the second reducing agent comprises urea; And / or, the second solvent includes ethanol and water; wherein the volume ratio of the ethanol to water is 3-5:5-8; And / or, the indium source includes any one or more combinations of indium nitrate hexahydrate, indium chloride, and indium sulfate; And / or, the drying treatment is performed at a temperature of 50-80° C. and for a time of 8-18 hours.
6. The laser preparation method according to claim 1, characterized in that: Specifically include: The first solid product and the aqueous solution of chloroplatinic acid hexahydrate precursor are mixed and stirred for 16 to 24 hours to form a suspension, and then the suspension is brushed on the surface of the substrate and dried naturally; wherein the thickness of the suspension brushed is 100 to 200 μm; And, the obtained carbon paper is subjected to laser irradiation treatment, and then washed and dried to obtain an atomically dispersed thermal catalyst; wherein the laser wavelength used in the laser irradiation treatment is 1064nm, the spot diameter is 260~520μm, the repetition frequency is 10-60kHz, the power is 40~100W, and the scanning speed is 1500~3000mm / s.
7. The laser preparation method according to claim 6, characterized in that: The mass volume ratio of the first solid product to the aqueous solution of chloroplatinic acid hexahydrate precursor is 0.30-0.63 g: 20-50 mL, and the concentration of the aqueous solution of chloroplatinic acid hexahydrate precursor is 5-25 mmol / L; And / or, the chloroplatinic acid hexahydrate precursor aqueous solution is a mixed solution of chloroplatinic acid hexahydrate and water, and the concentration of the chloroplatinic acid hexahydrate precursor aqueous solution is 5-25 mM; And / or, the substrate comprises carbon paper and / or carbon cloth; And / or, the drying process is performed at a temperature of 30-60° C. and for a time of 2-5 hours.
8. Atomically dispersed thermal catalyst prepared by the laser preparation method according to any one of claims 1 to 7, characterized in that: The thermal catalyst includes graphene, composite nano-oxide and Pt single atom / atom cluster; wherein the graphene forms a confined "sea" structure, the composite nano-oxide serves as a local "island" structure, and the Pt single atom / atom cluster is atomically dispersed on the "island" structure.
9. The atomically dispersed thermal catalyst according to claim 8, characterized in that: The composite nano-oxide is formed by In2O3 and Co3O4.
10. Use of the atomically dispersed thermal catalyst according to claim 8 or 9 in the preparation of methanol by hydrogenation of CO2.
Citation Information
Patent Citations
Method for preparing metal monatomic anchoring binary heterostructure catalyst
CN114899435A
Nickel-based selenide nano island confinement Pt monatomic catalyst and preparation method thereof
CN116273074A
Platinum-ruthenium bimetallic catalyst as well as preparation method and application thereof
CN117000233A
Method for laser solid-phase synthesis of metal-based nanoparticles and application thereof
CN118875298A
Catalytic plasmonic nanomaterial
WO2020176471A1